Weighted Maps: Location-aware Treemaps - Mohammad Ghoniem; Maël Cornil; Mickaël Stefas; Benoît Otjacques (Poster session of IEEE InfoVis'14, 2014)
The wide availability of quantitative geolocated structured data, e.g. census data, makes it desirable for classic tree visualizations to be location-aware. In this paper, we introduce a new treemap algorithm that produces rectangular cartograms consistently with the known location of data points on a geographic map.